2010
DOI: 10.1002/qj.633
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Northern Hemisphere stratospheric variability under increased CO2 concentrations

Abstract: † The contribution of J. Kettleborough was written in the course of his employment at the Met Office, UK, and is published with the permission of the Controller of HMSO and the Queen's Printer for Scotland.The robustness of stratospheric circulation changes under increased concentrations of carbon dioxide are investigated using the Met Office HadSM3-L64 model. Equilibrium climate change simulations employing forcing of two and four times pre-industrial CO 2 are presented, with particular focus on the temperatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
43
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(54 citation statements)
references
References 30 publications
10
43
1
Order By: Relevance
“…The studies of Sigmond et al (2004) and Gillett et al (2003) describe the effect of CO 2 doubling in terms of temperature and wind changes. Bell et al (2010) further show that the doubled CO 2 response in the UM model is robust, as a similar structure of the response, but with larger amplitude, is found under quadrupled CO 2 concentrations. Here we focus on changes in the stratospheric PV that are related to CO 2 doubling, and investigate to what extent these stratospheric changes influence the tropospheric zonal mean zonal wind response.…”
Section: Introductionsupporting
confidence: 54%
See 3 more Smart Citations
“…The studies of Sigmond et al (2004) and Gillett et al (2003) describe the effect of CO 2 doubling in terms of temperature and wind changes. Bell et al (2010) further show that the doubled CO 2 response in the UM model is robust, as a similar structure of the response, but with larger amplitude, is found under quadrupled CO 2 concentrations. Here we focus on changes in the stratospheric PV that are related to CO 2 doubling, and investigate to what extent these stratospheric changes influence the tropospheric zonal mean zonal wind response.…”
Section: Introductionsupporting
confidence: 54%
“…In general, a warming of the troposphere and a cooling of the stratosphere are observed in these simulations (e.g., Gillett et al, 2003;Sigmond et al, 2004;Bell et al, 2010). The response in the zonal wind, however, reflects the changes in the horizontal temperature gradient, which shows more variability among models.…”
Section: Introductionmentioning
confidence: 78%
See 2 more Smart Citations
“…For instance, Bell et al (2010) showed, using the Hadley Centre HadSM3-L64 model, that under four times pre-industrial CO 2 concentrations, the vortex would become more highly disturbed with an increased frequency of SSW events. In contrast, Rind et al (1998) reported a decrease in SSW frequency using the GISS global climate/middle atmosphere model with two times pre-industrial CO 2 concentrations.…”
Section: Introductionmentioning
confidence: 99%